Analysis of Taxable Income Calculation as a Basis for Determining the Amount of Income Tax Payable by PT Organo Science Laboratory - Dewantara, Tirta; Djoko Susilo, Danang; Dariansyah, Deddy (International Journal of Law Social Sciences and Management, 2026)
This study discusses Taxable Income as the basis for calculating the amount of tax payable by PT. Organo Science Laboratory in 2023. This study is motivated by the differences in the recognition of income and expenses commercially and fiscally. The purpose of this study is to analyze whether PT. Organo Science Laboratory has calculated Taxable Income in accordance with tax laws and regulations and to determine the obstacles faced and efforts made to overcome these obstacles. This study uses a descriptive analysis method, data collection techniques with literature studies, interviews and field studies. The results of this study indicate that the calculation of Taxable Income as a basis for determining the amount of Income Tax payable is not fully in accordance with applicable regulations, the obstacles faced by the company are the lack of human resources with a background in the field of taxation, resulting in a lack of understanding of tax regulations.